Effect of Fullerene C60 on Tomato Plants - Buziashvili, Anastasiia; Prylutska, Svitlana; Yemets, Alla (Innovative Biosystems and Bioengineering, 2024)
Background. Fullerenes, one of the allotropic forms of carbon, are the focus of intensive research in nanobiotechnology. Due to their unique physicochemical properties, there is growing interest in using them to enhance plant productivity and provide protection against various stresses. However, data on the effects of fullerenes on different plants are often contradictory. Objective. To investigate the effect of colloidal water-soluble fullerene C60 on various stages of tomato development. Methods. The study examined the influence of fullerene C60 (0–50 µg/ml) on the seed germination of the Money Maker cv. and the growth and development of seedlings and adult plants. For this purpose, morphophysiological parameters such as shoot and root length, number of lateral and adventitious roots, fresh weight, accumulation of photosynthetic pigments, and nitric oxide (II) were assessed. Results. Both positive and some phytotoxic effects of fullerene C60 on tomatoes were observed. Specifically, inhibition of seedling growth and a decrease in chlorophyll b and carotenoid content in adult plants were noted. Positive effects included an increased seed germination rate, higher fresh weight, greater length and number of adventitious roots in tomatoes grown in the presence of fullerene C60, and a higher nitric oxide (II) content in adult plants, which may contribute to enhanced stress resistance. Conclusions. Fullerene C60 at a concentration of 25 μg/ml has a predominantly positive effect on tomato development and may be considered a promising nanomaterial for plant biotechnology.